2018
DOI: 10.19080/jgwh.2018.11.555817
|View full text |Cite
|
Sign up to set email alerts
|

Can Ratings of Contraceptive Methods Motivate Women to Engage in Family Planning and Birth Control? A Review

Abstract: The aim of the paper is to determine as to whether or not the various ratings and rankings propounded by the World Health Organization (WHO), government agencies, professional organizations, and research institutes are reliable instruments for women in search of a contraceptive method and for health care providers who assist women in these pursuits. Method:To accomplish its goal, the review analyzes tables, surveys, and charts contained in the most frequently consulted sources of information, namely pertinent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…7. OCPs contain hormones that may increase cervical cell vulnerability to HPV infection, impair their capacity to clear infection, or make it simpler for HPV infection to initiate alterations that lead to cervical cancer [15]. Compared to my study, which found that only 3% of patients using injectable contraceptives had atypical smear results, one study found that current users of OCPs using it for more than 10 years, using it from around age 20-30 years, increase the cumulative incidence of CIN by the age 50 from 7.3 to 8.3 per 1000 in less developed countries [16].…”
Section: Discussionmentioning
confidence: 99%
“…7. OCPs contain hormones that may increase cervical cell vulnerability to HPV infection, impair their capacity to clear infection, or make it simpler for HPV infection to initiate alterations that lead to cervical cancer [15]. Compared to my study, which found that only 3% of patients using injectable contraceptives had atypical smear results, one study found that current users of OCPs using it for more than 10 years, using it from around age 20-30 years, increase the cumulative incidence of CIN by the age 50 from 7.3 to 8.3 per 1000 in less developed countries [16].…”
Section: Discussionmentioning
confidence: 99%